Role of VEGF in the differential growth between the fetal and placental ends of the umbilical cord (2019)
INTRODUCTION: The umbilical cord (UC) is a vital structure; its alterations affect the newborn and neurological impact can be permanent. Paradoxically, factors that determine it remain unknown. We explore the differential VEGF protein expression in the UC's proximal and distal portions in relation to the hypothesis that the UC has differential growth and that VEGF plays a role in it. METHODS: An observational analytical study was performed. One UC segment was taken proximal to fetus and another distal; both were randomly processed; VEGF immunohistochemical analysis was performed; two blinded pathologists read results. RESULTS: Forty-eight newborns were included. Protein expression between the two edges of the umbilical cord, in any kind of cells, was interpreted. Endothelium, amnion, and stromal cells expressed VEGF; the first two were not different between opposite ends. Stromal cells had differential expression: higher in the proximal to the fetus portion. CONCLUSION: Knowledge of molecular factors is necessary. UC cells widely expressed VEGF, possibly contributing to UC growth. Even though stromal cell expression was different, the interaction with activity close to the fetus must be explored. © 2019 - IOS Press and the authors. All rights reserved.